(untitled) (Comparative Professional Pedagogy, 2023)
The article is devoted to the study of the system of dance education in the USA. It is found that dance education is an important artistic and educational resource for the harmonious physical, spiritual and cultural development of the individual. It is revealed that the development of dance education is determined by modern socio-cultural values and artistic needs of the American multicultural society. As a systemic phenomenon, dance education nowadays is characterized by the multi-vector nature of dance art, the integration of philosophical, pedagogical, sociological, valeological, kinesiological, psychological, artistic, cultural ideas, theories and concepts. It is noted that the system functions at different levels (legislative, regulatory, managerial, institutional, substantive, technological), which serve as its structural components. The content of each component of the system is thoroughly analyzed. The content of the Professional Standards for Teaching Dance Art is studied and summarized, the requirements and criteria for the professional competence of choreography teachers in eight aspects are clarified. It is established that the system of dance education performs certain functions: social, value-content, organizational, monitoring and prognostic. It is found that the system of dance education in the USA has both positive aspects of development and challenges that need to be solved. The latter include inconsistency in the educational programs of training and certification of choreography teachers; the lack of choreography parity in school art education; an urgent need for qualified creative dance teachers; insufficiently substantiated mechanisms for certification of private dance studios and schools. It is concluded that the system of dance education in the USA is specific, has positive aspects and problems, functions at different levels, includes interconnected and interacting systemic components that ensure dynamic development.